2020
DOI: 10.1126/sciadv.aba2331
|View full text |Cite
|
Sign up to set email alerts
|

All twist and no bend makes raft edges splay: Spontaneous curvature of domain edges in colloidal membranes

Abstract: Using theory and experiments, we study the interface between two immiscible domains in a colloidal membrane composed of rigid rods of different lengths. Geometric considerations of rigid rod packing imply that a domain of sufficiently short rods in a background membrane of long rods is more susceptible to twist than the inverse structure, a long-rod domain in a short-rod membrane. The midplane tilt at the interdomain edge forces splay, which, in turn, manifests as spontaneous edge curvature with energetics con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…Recent theoretical and experimental work 51–53 has also concluded that the volume change upon twist plays a crucial role in determining the geometry and stability of colloidal membranes of rod-like particles. The geometric frustration between double-twist and splay causes the twisted monolayer to have a hyperbolic edge ( i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical and experimental work 51–53 has also concluded that the volume change upon twist plays a crucial role in determining the geometry and stability of colloidal membranes of rod-like particles. The geometric frustration between double-twist and splay causes the twisted monolayer to have a hyperbolic edge ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Only when the perpendicular fluctuations of the rods are suppressed and their centers are confined at the 2D midplane (which is the same as the theoretical model in ref. 53), does our monolayer exhibit a hyperboloid-like shape [Fig. S5(b)†].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, this means that the characteristic curves from the z = 0 plane never intersect. In a finite geometry, it is possible that a virtual intersection could occur outside the sample as discussed, for instance, in [30] in the context of viral rafts. In that and other cases (15) would be modified by the sample size.…”
Section: Geometry and Stabilitymentioning
confidence: 99%
“…For example, one could stack these structures, forming something akin to a hexagonal columnar phase or a Moiré phase (24). Although this would introduce bend defects, it would lower the ever-growing splay of tall diabolic domains (25). Another possibility is to construct an Apollonian packing of circles in the z = 0 plane, leading to an intricate structure of skew domains.…”
Section: Diabolo Domainsmentioning
confidence: 99%